PROFESSIONAL COMPETENCES OF A BEGINNING MASTER OF VOCATIONAL EDUCATION AND ITS REFLECTION - CELLAROVA, Lydia (Journal of Technology and Information Education, 2010)
In the article we point actual requirements for professional competences of a teacher, acquaint with proposal of professional standards and competences of beginning master of vocational education and brief results of the survey, in which students of the last year of practical preparation pedagogy study rate their competences.
Keywords: professional competences; master of vocational training; reflection; survey